(untitled) - Yaghjian, Lucretia B. (U.S.A., 2006)
In its creative integration of the disciplines of writing, rhetoric, and theology, 'Writing Theology Well' provides a standard text for theological educators engaged in the teaching and mentoring of writing across the theological curriculum. As a theological rhetoric, it will also encourage excellence in theological writing in the public domain by helping to equip students for their wider vocations as writers, preachers, and communicators in a variety of ministerial and professional contexts.
Keywords: Theology